2015
DOI: 10.5433/1679-0359.2015v36n6supl2p4493
|View full text |Cite
|
Sign up to set email alerts
|

Seminal and spermatic characteristics of fresh semen and the effects of sperm cooling in Steindachneridion melanodermatum (Garavello, 2005)

Abstract: This study describes the seminal and spermatic characteristics of fresh semen of Steindachneridion melanodermatum and investigates the effects of dilution, temperature, and storage period on its spermatic parameters. Sperm samples were collected from nine hormonally-induced males. The following parameters in fresh sperm were analyzed: seminal plasma osmolality (OSM), seminal pH, sperm motility (MOT), sperm velocity (SV) (including sperm curvilinear velocity (VCL), sperm straight-line velocity (VSL), and sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
4
2
Order By: Relevance
“…The analysis of motility duration of S. melanodermatum revealed similar results with activation using tank water (154.4±72.6 seconds) and distilled water (149.0±77.5 seconds) (Table 1). These values were higher than those obtained by Marcos et al (2015) for S. melanodermatum, which found an average of 79.31 seconds, most probably due to the higher dilution we used in the present study.…”
Section: Resultscontrasting
confidence: 87%
See 4 more Smart Citations
“…The analysis of motility duration of S. melanodermatum revealed similar results with activation using tank water (154.4±72.6 seconds) and distilled water (149.0±77.5 seconds) (Table 1). These values were higher than those obtained by Marcos et al (2015) for S. melanodermatum, which found an average of 79.31 seconds, most probably due to the higher dilution we used in the present study.…”
Section: Resultscontrasting
confidence: 87%
“…Specimens maintained in captivity with adequate feed and water provide good results (Table 1). Marcos et al (2015), observed for this species in October higher volumes (mean of 11.7 mL) when compared with the present experiment. Such a difference may arise because January those fish may be at the end of the spawning season, as observed in other Neotropical species which concentrates the reproduction during the October to December (Godoy, 1975;Vazzoler, 1996;Agostinho et al, 2004).…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations